Characterization of N-Acetylglucosamine Biosynthesis in Pneumocystis species. A New Potential Target for Therapy - Kottom, Theodore J. (Am J Respir Cell Mol Biol, 2017)
N-acetylglucosamine (GlcNAc) serves as an essential structural sugar on the cell surface of organisms. For example, GlcNAc is a major component of bacterial peptidoglycan, it is an important building block of fungal cell walls, including a major constituent of chitin and mannoproteins, and it is also required for extracellular matrix generation by animal cells. Herein, we provide evidence for a uridine diphospho (UDP)–GlcNAc pathway in Pneumocystis species. Using an in silico search of the Pneumocystis jirovecii and P. murina (Pm) genomic databases, we determined the presence of at least four proteins implicated in the Saccharomyces cerevisiae UDP-GlcNAc biosynthetic pathway. These genes, termed GFA1, GNA1, AGM1, and UDP-GlcNAc pyrophosphorylase (UAP1), were either confirmed to be present in the Pneumocystis genomes by PCR, or, in the case of Pm uap1 (Pmuap1), functionally confirmed by direct enzymatic activity assay. Expression analysis using quantitative PCR of Pneumocystis pneumonia in mice demonstrated abundant expression of the Pm uap1 transcript. A GlcNAc-binding recombinant protein and a novel GlcNAc-binding immune detection method both verified the presence of GlcNAc in P. carinii (Pc) lysates. Studies of Pc cell wall fractions using high-performance gas chromatography/mass spectrometry documented the presence of GlcNAc glycosyl residues. Pc was shown to synthesize GlcNAc in vitro. The competitive UDP-GlcNAc substrate synthetic inhibitor, nikkomycin Z, suppressed incorporation of GlcNAc by Pc preparations. Finally, treatment of rats with Pneumocystis pneumonia using nikkomycin Z significantly reduced organism burdens. Taken together, these data support an important role for GlcNAc generation in the cell surface of Pneumocystis organisms.